ANALISIS EFISIENSI PENGGUNAAN FAKTOR PRODUKSI PADA USAHA PERKEBUNAN KOPI DI KECAMATAN SUSUT, KABUPATEN BANGLI - Ida Ayu Nyoman Saskara, Ida Bagus Abhimanyu,; Saskara, Ida Ayu Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 9 No 10 (2020): VOL 9 NO 10, OKTOBER 2020 (2152 - 2389), 2020)
Coffee one of plantation in Indonesia. Bangli Regency one of Arabica coffee producing areas. The purpose this study to analyze 1) effect using production factors, land area, capital, and labor simultaneously on amount coffee production in Susut District, Bangli 2) effect using production factors, land area, capital and labor partially on amount production coffee in Susut District, Bangli 3) level efficiency in coffee plantation activities in Susut District, Bangli 4) the scale of coffee production in Susut District, Bangli. Data used primary and secondary with sample 69 farmers, multiple linear regression analysis techniques. The results 1) Land area, capital and labor simultaneously have significant effect on coffee production in Susut District, Bangli 2) Land area, capital, and labor, partially significant positive effect on coffee production in Susut District, Bangli 3) Scale economy in condition of increasing returns to scale 4) Level efficiency the use capital production factors, and workforce is efficient condition but not maximized. The use of land area production factors is inefficient, so it does not need to be increased. The variable with the most dominant influence is the variable of land area, which is equal to 0.732.